Analysis of Highway Slope Failure by Using Stereographic Projection Method - Bhandari, Bharat Prasad; Joshi, Tark Raj (Journal of Engineering Technology and Planning, 2019)
This study was conducted at the Bhasu Bhir of Kailali district in the Far-western Province, along the Khanidanda-Sahajpur road section of Bhimdatta pant highway. The main objective of this study is to identify the potential slope failure area and assess the major control factors along the road section. To accomplish the objective, the dip amount and dip direction of major discontinuity was measured in the field along with hill slope and hill slope direction. The data of 40 locations were analyzed by using stereographic projection method. The result was obtained by using Dips 6.0 software. The major slope failures obtained on the area were wedge failure and plane failure. The hill slope geometry, joint status and rock geometry are found major controlling factors for the slope failure in the study area.